Characterizing ground ice content and origin to better understand the seasonal surface dynamics of the Gruben rock glacier and the adjacent Gruben debris-covered glacier (southern Swiss Alps) - J. Wee; S. Vivero; T. Mathys; C. Mollaret; C. Hauck; C. Lambiel; J. Beutel; W. Haeberli (The Cryosphere)
Over the recent years, there have been focused international efforts to coordinate the development and compilation of rock glacier inventories. Nevertheless, in some contexts, identifying and characterizing rock glaciers can be challenging as complex conditions and interactions, such as glacier–rock-glacier interactions, can yield landforms or landform assemblages that are beyond a straightforward interpretation and classification through ordinary visual means alone. To gain a better understanding of the spatial and temporal complexity of the ongoing processes where glacier–permafrost interactions have occurred, the characterization of the subsurface of the Gruben rock glacier and its adjacent complex contact zone with the then more extended Little Ice Age Gruben glacier is quantitatively assessed using a petrophysical joint inversion (PJI) scheme, based on electrical resistivity (ERT) and refraction seismic (RST) data. Surface dynamics are assessed using both in situ and close-range remote sensing techniques to monitor daily and seasonal displacements and to monitor landform-wide surface changes at high spatial resolution, respectively. Both the geophysical and geodetic surveys allowed two zones to be identified: the rock glacier zone and the complex contact zone where both permafrost and embedded surface ice are present. In the complex contact zone extremely high ice contents (estimated up to 85 %) were found. Widespread supersaturated permafrost conditions were found in the rock glacier zone. Surface displacement rates in this zone are typical of permafrost creep behaviour, with a gradual acceleration in late spring and a gradual deceleration in winter. Moreover, the coherent nature of the rock glacier zone surface deformation contrasts with the back-creeping and slightly chaotic surface deformation of the complex contact zone. Favouring a multi-method approach allowed a detailed representation of the spatial distribution of ground ice content and origin, which enabled us to discriminate glacial from periglacial processes as their spatio-temporal patterns of surface change and geophysical signatures are (mostly) different.